Exploring collaborative strategies to improve patient safety in healthcare organizations: A qualitative study - Mohammad Esmaeil Hejazi; Ghasem Alizadeh-dizaj; Shiva Khoshsirat; Samira Raoofi; Akbar Javan Biparva (PLoS ONE, 2026)
Background Patient safety remains a critical concern in healthcare, necessitating the exploration of collaborative approaches to enhance care quality and outcomes. This qualitative study delves into the significance of interprofessional collaboration, leadership support, patient engagement, and safety culture in driving patient safety initiatives within healthcare settings. Method This qualitative phenomenological approach, involving in-depth interviews and document analysis, was conducted to explore the perspectives of healthcare professionals, administrators, patients, policymakers, and researchers involved in patient safety initiatives. Thematic analysis was employed to identify and organize recurring patterns in the data, while interpretive phenomenological analysis was utilized to gain a deeper understanding of participants’ lived experiences. This dual approach revealed key themes related to teamwork, communication, leadership, patient engagement, and best practices in patient safety. Results The study revealed that interprofessional collaboration is widely recognized as vital for patient safety, with participants highlighting the importance of effective communication, shared decision-making, and mutual respect among healthcare professionals. Leadership support, organizational structures, and a culture of safety emerged as key enabling factors. Despite the benefits, challenges such as hierarchy, siloed communication, resource constraints, and resistance to change remain significant barriers. Strategies including regular interdisciplinary training, patient engagement initiatives, leveraging technology, and continuous quality improvement processes were identified as effective ways to strengthen collaborative practices. Conclusion Promoting interprofessional collaboration, strong leadership, and a robust safety culture are essential for improving patient safety outcomes. Overcoming systemic and interpersonal barriers requires targeted interventions at both individual and organizational levels, with ongoing education, patient participation, and data-driven feedback playing crucial roles in sustaining collaborative efforts. These insights support the adoption of integrated approaches to foster safer and higher-quality care across healthcare settings.